DEFORMATION ENERGY OF VEHICLES IN ROAD TRAFFIC ACCIDENTS - PERLOV, VIKTOR; KYRYTSIA, INNA; PRADIVLIANNYI, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In this work, a method of determining the deformation energy of vehicle structural elements deformed as a result of a traffic accident has been developed, as well as a method of determining the deployment parameters of vehicle airbags is given.The determination of the energy of deformation in the structural elements of vehicles during road traffic accidents (RTAs) plays a significant role in understanding collision mechanisms and the consequences of damage. One factor influencing the deformation of vehicles is the change in metal hardness due to deformation.One way to determine the energy of deformation is to analyze the change in metal hardness due to deformation. Applying hardness measurements to damaged vehicle components provides information about the level of deformation, reflected in the change in material hardness.To perform such measurements, portable hardness testing devices are often used, which can directly measure the metal hardness at the accident scene. These devices are based on various measurement methods, such as indentation methods or rebound methods. The obtained data on the change in metal hardness are used to calculate the energy of deformation. With this information and the use of appropriate mathematical models, it is possible to determine the energy absorbed by the material during deformation. This deformation energy is an indicator of the extent of damage and mechanical impact experienced by the vehicle.Estimating deformation energy is critical to understanding the mechanisms of road traffic accidents (RTAs) and their consequences. It can help establish collision forces, vehicle speeds, and other parameters necessary for accident investigation. In addition, the determination of deformation energy can be used to assess the safety of vehicle structures and develop measures to improve their stability and protect passengers. The combination of several methods allows you to refine the energy absorption coefficients in computing programs.
Keywords: road traffic accidents (RTAs); deformation energy; structural safety; metal hardness; airbag